Science-and-Religion/Spirituality/Theology Dialogue: What for and by Whom? - Reich, K. Helmut (Zygon, 2008)
Abstract. In recent years the science-and-religion/spirituality/theology dialogue has flourished, but the impact on the minds of the general public, on society as a whole, has been less impressive. Also, religious believers and outspoken atheists face each other without progressing toward a common understanding. The view taken here is that achieving a more marked impact of the dialogue would be beneficial for a peaceful survival of humanity. I aim to argue the why and how of that task by analyzing three possible purposes of the dialogue and their logical interdependence, suggest conceivable improvements of the quality and extent of the current efforts toward a negotiated action plan, and consider an enlargement of the circle of the actors involved. The dialogue that has been carried on between science and religion/spirituality/theology could be expanded and usefully applied to some major problems in the present world.